DYSTOCIA due to Perosomus Elumbis in a Goat - SUTHAR, V S; PARMAR, A P; PANCHAL, M T; SHAH, R G; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
A stillborn Perosomus elumbis male kid encountered in anterior longitudinal presentation withpostural defects of extremities in a goat was delivered by lubrication, correction and manual traction.
Keywords: Dystocia; Goat; Perosomus elumbis